Resilience Factors Contributing to Mental Health Among People Affected by the Fukushima Disaster: Development of Fukushima Resilience Scale - Takebayashi, Yui; Maeda, Masaharu; Orui, Masatsugu; Nakajima, Satomi; Momoi, Maho; Ito, Akiko; Sato, Hideki; Yasumura, Seiji; Ohto, Hitoshi (Frontiers in Public Health, 2020)
Aim: The aims of the present study were to develop and validate a psychological resilience scale reflecting the specificity of the Fukushima disaster, and to examine the effects of this scale on mental health. Methods: The Fukushima Resilience Scale was developed based on data obtained from semi-structured interviews with seven people who had lived in the affected area of Fukushima Prefecture at the time of the disaster. The reliability and validity of the scale were then examined in cross-sectional studies conducted on 500 evacuees through an epidemiological mail survey. To examine the effects of the scale and disaster-related factors on the general mental health status of the respondents, a logistic regression analysis was performed using the six-item Kessler psychological distress scale. Results: The newly developed scale consisted of a four-factor structure: “coping with stigma-related issues”, “sharing experiences of the disaster”, “action-oriented approach”, and “sense of support”. Internal consistency coefficients ranged from 0.66 to 0.79. The multivariable logistic regression analysis showed that the only significant association was between “action-oriented approach” (odds ratio = 1.26) and respondents with a K6 score <5 points. Conclusion: The reliability and concurrent validity of the new developed scale in residents of the evacuation area of Fukushima Prefecture were acceptable. A significant association was found between “action-oriented approach” and good mental health among the evacuees, which suggests that this may improve resilience among people affected by the Fukushima disaster.